STUDI KASUS PROSEDUR PEMERIKSAAN CT SCAN UROGRAFI KLINIS BATU GINJAL DI INSTALASI RADIOLOGI RSUD CARUBAN - Meva Relita Setia Putri; Anisa Nur Istiqomah; Ildsa Maulidya Mar’atus Nasokha (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
ABSTRACT Kidney stones are among the most common urinary tract diseases and are associated with a high incidence and recurrence rate, requiring accurate diagnostic imaging for appropriate clinical management. Non-contrast CT urography has become one of the primary imaging modalities because it provides a comprehensive evaluation of the urinary system, including the application of the Curved Planar Reformation (CPR) technique to visualize the ureters along their anatomical course. This study aimed to describe the examination procedure of non-contrast CT urography, its role in establishing the diagnosis of kidney stones, and the rationale for using the Curved Planar Reformation (CPR) technique at the Radiology Department of RSUD Caruban. A qualitative study with a case study approach was conducted involving one clinical case of kidney stones through observation, interviews, and documentation. The participants consisted of three radiographers, one radiologist, and one urologist. The results showed that the examination procedure included patient preparation, equipment and material preparation, examination technique, scanning parameter settings, image reconstruction, and the application of the Curved Planar Reformation (CPR) technique. Non-contrast CT urography played a crucial role in identifying the location, size, and density of stones, as well as associated urinary tract complications, while the CPR technique improved ureteral visualization, facilitating stone detection and supporting more accurate image interpretation. In conclusion, non-contrast CT urography combined with the Curved Planar Reformation (CPR) technique provides comprehensive diagnostic information to support the accurate diagnosis of kidney stones. ABSTRAK Batu ginjal merupakan salah satu penyakit saluran kemih dengan angka kejadian dan kekambuhan yang tinggi sehingga memerlukan pemeriksaan diagnostik yang akurat. CT Scan urography non kontras menjadi salah satu modalitas pencitraan utama karena mampu mengevaluasi sistem urinaria secara menyeluruh, termasuk melalui penerapan teknik Curved Planar Reformation (CPR) untuk memvisualisasikan ureter sesuai dengan jalur anatomisnya. Penelitian ini bertujuan mendeskripsikan prosedur pemeriksaan CT Scan urography non kontras, peranannya dalam menegakkan diagnosis batu ginjal, serta alasan penggunaan teknik Curved Planar Reformation (CPR) di Instalasi Radiologi RSUD Caruban. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus terhadap satu kasus klinis batu ginjal melalui teknik observasi, wawancara, dan dokumentasi. Informan penelitian terdiri atas tiga radiografer, satu dokter spesialis radiologi, dan satu dokter spesialis urologi. Hasil penelitian menunjukkan bahwa prosedur pemeriksaan meliputi persiapan pasien, persiapan alat dan bahan, pelaksanaan teknik pemeriksaan, pengaturan parameter scanning, rekonstruksi citra, serta penerapan teknik Curved Planar Reformation (CPR). CT Scan non kontras berperan penting dalam mengidentifikasi lokasi, ukuran, densitas batu, serta komplikasi pada saluran kemih, sedangkan teknik CPR meningkatkan visualisasi ureter sehingga mempermudah identifikasi batu dan mendukung interpretasi hasil pemeriksaan secara lebih akurat. Dengan demikian, pemeriksaan CT Scan urography non kontras yang dipadukan dengan teknik Curved Planar Reformation (CPR) mampu memberikan informasi diagnostik yang komprehensif dalam mendukung penegakan diagnosis batu ginjal.